Investigation of Preservice Teachers’ Knowledge Related to Basic Concepts of Environmental Phenomenon - Doğan, Yakup (Journal of History Culture and Art Research, 2018)
The purpose of this study is to reveal knowledge of preservice preschool teachers about the basic concepts of environmental phenomenon. Phenomenology, one of the qualitative research method, was used in the study. The study group included 62 preservice teachers (54 female and 8 male) who were studying preschool education at one of the state universities located in the Southeastern Anatolia Region in Turkey. An open-ended questionnaire was prepared and used by the researcher to collect data. Content analysis technique was used to analyze the data obtained from study. According to the results of the study, a small number of the preservice teachers were determined to have sufficient knowledge about the basic concepts related to the environmental phenomenon. Similarly, a minority of the preservice teachers were found to have acceptable knowledge. However, the majority of preservice teachers were found to have inadequate/incorrect knowledge about basic environmental concepts. It can be said that this situation which may be based on the fact that the preservice teachers had not taken courses related to the environment, had not participated in the activities related to the environment and had not become members to nongovernmental organization related to the environment. Based on the results of this study, it can be recommended that the curricula could be enriched in relation to the environment and ecology, hands-on environmental activities could be implemented and participation of nongovernmental organizations’ activities may be encouraged.